Apoplexy in Optochiasmatic Cavernous Hemangioma Causing Visual Diminution: A Case Report - Sumit Bansal; Ashish Suri; Vaishali Suri; Aanchal Kakkar (Indian Journal of Neurosurgery)
Abstract This report concerns a woman who presented with abrupt onset of monocular visual symptoms accompanied by an intense holocranial headache, diagnosed as optic chiasm apoplexy caused by a cavernous hemangioma of the optic chiasm. The surgical and histologic findings demonstrated a cavernous hemangioma. The lesion was removed completely without any noticeable bleeding. The preoperative visual deficit improved after surgery.